2005
DOI: 10.1110/ps.051363105
|View full text |Cite
|
Sign up to set email alerts
|

Structural model of the amino propeptide of collagen XI α1 chain with similarity to the LNS domains

Abstract: Fibrillar collagens are the principal structural molecules of connective tissues. The assembly of collagen fibrils is regulated by quantitatively minor fibrillar collagens, types V and XI. A unique amino-terminal propeptide domain of these collagens has been attributed this regulatory role. The structure of the amino terminal propeptide has yet to be determined. Low sequence similarity necessitated a secondary structure-based method to carry out homology modeling based upon the determined structure of LNS fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 42 publications
0
16
0
2
Order By: Relevance
“…The common Npp site is positioned in a beta‐strand in residues 147–152 and conforms to the CW XBBBXXBX motif in which the basic amino acids are exclusively lysines (Fallahi et al . ; Warner et al . ).…”
Section: Diffusion Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The common Npp site is positioned in a beta‐strand in residues 147–152 and conforms to the CW XBBBXXBX motif in which the basic amino acids are exclusively lysines (Fallahi et al . ; Warner et al . ).…”
Section: Diffusion Effectsmentioning
confidence: 99%
“…There is one common heparin-/HS-binding site in the NTDs of these collagens located in the so-called amino propeptide (Npp) region towards the NT, and an additional site is in an alternatively spliced region of collagen XI near to the collagenous domain (Figure 14a). The common Npp site is positioned in a beta-strand in residues 147-152 and conforms to the CW XBBBXXBX motif in which the basic amino acids are exclusively lysines (Fallahi et al 2005;Warner et al 2006). In contrast, the site in the variable region of collagen XI NTD is a long positively charged sequence containing multiple clusters of arg/lys residues (Warner et al 2006) somewhat analogous to the unique HS-binding region in SDF1-gamma.…”
Section: Heparan Sulphate/heparin Binding In the N-terminal Domains (mentioning
confidence: 99%
“…Simulated annealing and genetic algorithms have been extensively used to dock GAGs to their putative proteins or receptors (137,144,(154)(155)(156)(157)(158). It is clear that the prediction of binding energies of heparin and related sulphated GAGs to their biological targets requires a large number of docking evaluations in order to achieve energy convergence and sufficient conformational sampling.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…This differential regulation has been previously demonstrated in smooth muscle cells in the tunica media of ATAAs [19, 20] and in aortic smooth muscle cells in culture [17], and has been suggested as a possible mechanism modulating ECM remodeling. Recent studies have shown that the amino-terminal propeptide of collagen α1(XI) contains a well-characterized heparin binding domain [21, 22]. This heparin binding domain has been shown to interact with specific integrin receptors that promote the regulation of expression and activity of matrix metalloproteinases (MMPs) [23].…”
Section: Commentmentioning
confidence: 99%